The Allure of Heavenly Mother, from South Korea to South Africa: Epistemological Authority at the World Mission Society Church of God - Bafford, Douglas (Nova religio, 2025)
The World Mission Society Church of God (WMSCOG) is a transnational Sabbatarian religion that emerged in South Korea after the 1985 death of its founding messianic figure, Ahn Sahng-hong. With a strong emphasis on proselytization, the organization has achieved widespread adoption in diverse national settings, despite having received relatively little attention in anglophone scholarly literature. Drawing on ethnographic encounters with this movement and its preachers in an urban South African context, I describe tenets of their theology and the parallels between their form of directed scriptural study and techniques found in related groups, based on a principle of hidden knowledge revealed through prophecy and typological interpretation. The epistemology of its core theological methods is similar to that of evangelical Christianity, which commands a dominant presence in the region. The WMSCOG’s heterodox Christology and Korean cultural roots, while perceived as counterintuitive for potential South African converts, bolster the group’s authority as a restoration of holiness, signs of which are taught to be analogically discernible in adherents’ everyday environments.